An Evaluation of Organic Growth, and Mergers and Acquisitions as Strategic Growth Options in the Nigerian Banking Sector - Jimmy, Anthony Efe (2008)
In response to a Central Bank of Nigeria's policy to increase the minimum paid-up share capital requirement of Nigerian banks from N2 billion to N25 billion in July 2004, with December 31, 2005 as deadline, more than half of the 89 banks in Nigeria as at July 2004 were engaged in one form of merger and acquisition, some sourced for additional capital through public offering of their share, and others a combination of merger and acquisition and public offering. The Central Bank of Nigeria's policy to increase the paid-up share capital was to amongst other things to strengthen the financial capacity and effectiveness of the Nigerian banking sector. This dissertation evaluated organic growth, and mergers and acquisitions as strategic growth options in the Nigerian banking sector, with a view to ascertaining which of the growth strategies result in superior financial performance. Access Bank and Zenith Bank were used as case studies. Through the use of various financial ratios in analysing five years financial statements and other relevant information on both banks from 2003 to 2007, the analysis suggests a mixed result: Access Bank that pursued M&A witnessed a faster growth rate, whereas Zenith Bank that pursued organic growth was able to sustain its quality performance trends and achieved a slower growth rate during the period under review, in line with past literatures on mergers and acquisitions, and organic growth respectively.